Analisis Antena Mikrostrip Array Bentuk Lingkaran Dan Persegi Panjang Menggunakan Simulasi Untuk Aplikasi LTE Frekuensi 2.3 Ghz - Rio Juli Hendra; Yusnita Rahayu; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Technology Long Term Evolution (LTE) has a high-speed data transfer, large range of access and mobility. Long Term Evolution (LTE) antenna requires small dimensions and integrates easily. Therefore, microstrip antenna is a good candidate for this application. This paper discusses the design of a single antenna element and a fourth element circular and rectangular patch, microstrip patch antenna which can be used for LTE applications in the 2.3 GHz (2.3 to 2.36 GHz). Microstrip antenna designed using microstrip line technique. Design and simulation of microstrip antenna requires Ansoft HFFS paragraph 13. The simulation results show that the antenna can operate at frequencies from 2.3 to 2.36 GHz. Impedance bandwidth of 163 MHz value (2.252 to 2.415 GHz) or 6.9% at VSWR ≤ 1.9 and gain is 4,704 dBi.Keywords : Long Term Evolution (LTE ), Planar Array, Microstrip Line, VSWR and Gain